Disease Tolerance Mediated by Phosphorylated Indoleamine-2,3 Dioxygenase Confers Resistance to a Primary Fungal Pathogen - de Araújo, Eliseu Frank; Loures, Flávio Vieira; Feriotti, Cláudia; Costa, Tania; Vacca, Carmine; Puccetti, Paolo; Romani, Luigina; Calich, Vera Lúcia Garcia (Frontiers in Immunology, 2017)
Resistance to primary fungal pathogens is usually attributed to the pro-inflammatory mechanisms of immunity conferred by interferon- activation of phagocytes that control microbial growth whereas susceptibility is attributed to anti-inflammatory responses that deactivate immunity. This study challenges this paradigm by demonstrating that resistance to a primary fungal pathogen such as Paracoccidiodes brasiliensis can be mediated by disease tolerance, a mechanism that preserves host fitness instead of pathogen clearance. Among the mechanisms of disease tolerance described, a crucial role has been ascribed to the enzyme indoleamine 2,3 dioxygenase (IDO) that concomitantly controls pathogen growth by limiting tryptophan availability and reduces tissue damage by decreasing the inflammatory process. Here we demonstrated in a pulmonary model of paracoccidioidomycosis that IDO exerts a dual function depending on the resistant pattern of hosts. IDO activity is predominantly enzymatic and induced by IFN- signaling in the pulmonary dendritic cells (DCs) from infected susceptible (B10.A) mice, whereas phosphorylated IDO (pIDO) triggered by TGF- activation of DCs functions as a signaling molecule in resistant mice. IFN- signaling activates the canonical pathway of NFB that promotes a pro-inflammatory phenotype in B10.A DCs that control fungal growth but ultimately suppress T cell responses. In contrast, in A/J DCs IDO promotes a tolerogenic phenotype that conditions a sustained synthesis of TGF-β and expansion of regulatory T (Treg) cells that avoid excessive inflammation and tissue damage contributing to host fitness. Therefore, susceptibility is unexpectedly mediated by mechanisms of pro-inflammatory immunity that are usually associated with resistance, whereas genetic resistance is based on mechanisms of disease tolerance mediated by pIDO, a phenomenon never described in the protective immunity against primary fungal pathogens.